Design and implementation of an industrial security system using color cameras - Ouhoud, Amina; Hakim Guezzen, Amine (Institute of Advanced Engineering and Science, 2025)
This paper examines the design, development, and implementation of a modern industrial security system that integrates color cameras to enhance surveillance and improve safety. The system leverages cutting-edge technologies to detect intrusions and incidents with greater accuracy, which significantly strengthens the security of industrial sites. The study focuses on key stages of the project, including the design, installation, and operational processes, while addressing the challenges encountered during these phases. The integration of color cameras provides clearer and more precise monitoring, allowing for quicker detection and response to potential threats, thus reducing risks effectively. Our results demonstrate that the system greatly improves surveillance efficiency, providing a reliable and robust solution tailored to the security demands of industrial environments. This research offers in-depth insights into the system’s design and functionality, showcasing its critical role in safeguarding industrial facilities. Overall, the proposed solution is an essential tool for enhancing safety protocols and risk management strategies, contributing to more secure industrial sites.